2016
DOI: 10.1161/hypertensionaha.115.06486
|View full text |Cite
|
Sign up to set email alerts
|

Acute Response to Unilateral Unipolar Electrical Carotid Sinus Stimulation in Patients With Resistant Arterial Hypertension

Abstract: Bilateral bipolar electrical carotid sinus stimulation acutely reduced muscle sympathetic nerve activity (MSNA) and blood pressure (BP) in patients with resistant arterial hypertension but is no longer available. The second-generation device utilizes a smaller unilateral unipolar disk electrode to reduce invasiveness while saving battery life. We hypothesized that the second-generation device acutely lowers BP and MSNA in treatment-resistant hypertensive patients. Eighteen treatment-resistant hypertensive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 38 publications
1
47
0
1
Order By: Relevance
“…Titrating BAT neo to chronically tolerable levels may be associated with reduction in efficacy compared with BAT rheos [45]. Thereby, it must be considered that all patients in the present study were treated with BAT neo.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Titrating BAT neo to chronically tolerable levels may be associated with reduction in efficacy compared with BAT rheos [45]. Thereby, it must be considered that all patients in the present study were treated with BAT neo.…”
Section: Discussionmentioning
confidence: 94%
“…Recently, it was suggested that BAT rheos and neo may differ in terms of acute efficacy [45]. Titrating BAT neo to chronically tolerable levels may be associated with reduction in efficacy compared with BAT rheos [45].…”
Section: Discussionmentioning
confidence: 99%
“…45 Notably, a recent acute study in patients employing 2 min periods of unilateral carotid sinus activation suggested that the new electrode design may diminish efficacy and tolerability. 49 However, this has not been our experience when using the Barostim Neo system during chronic bilateral carotid sinus activation in canines. 33,50 Randomized controlled trials are needed to thoroughly evaluate whether the Barostim Neo electrode system may have clinical utility in managing RHT.…”
Section: Discussionmentioning
confidence: 95%
“…In the first study, Heusser et al found that acute stimulation of the carotid sinus via a unilaterally implanted electrode, acutely lowered both systolic and diastolic BP in 18 patients with uncontrolled resistant hypertension. 28 There was not a significant change in muscle sympathetic nerve activity (MSNA), but overall, reductions in diastolic BP did correlate with reductions in MSNA. There was a wide range in the magnitude of BP and MSNA reduction following acute carotid sinus stimulation and about two-thirds of the subjects experienced stimulation-related adverse effects, necessitating reduction in the stimulation intensity.…”
Section: Baroreflex Activation Therapymentioning
confidence: 92%